(untitled) (Филолошки студии, 2019)
The city of poets and linden trees, Stara Zagora, is one of the eminent Bulgarian cultural centers that has contributed many a name for Bulgaria’s national literature, fostering many prominent poets. These include: Kiril Hristov, Nikolaj Liliev, Dimitar Povrzachov, Geo Milev, Ivan Hadzihristov, Ivan Mirchev. As a part of the large group of Macedonian denizens, within the city, who arrived through the semblance of many re-mappings of historical borders, whilst seeking one’s own sense of belonging, a few literary names crop up. During the 1930s, a small group of authors is assembled, a group which will leave a lasting mark on the city’s literary life, and in the interim years between the two World Wars, these men will leave their own mark on the cultural life within the greater Bulgarian state. The first indications of such literary activity, in regards to the Macedonian Poetry Circle from Stara Zagora, come to us though Konstantin Konjarov. In the second half of the 1920s, a youth called Hristo Ognjanov, born in 1911, in the village of Tresonche, in Macedonia, comes to Stara Zagora. He matches the success of his brother Boris, finishing the five-year high school for a period of three years. The all-boys high school in Stara Zagora, ‘Ivan Vazov’, is characterized for its military discipline, but at the same time offering a rich cultural life. Beginning with 1921, a literary circle, with its own publication titled ‘Echo’ commenced with its work. Ognjanov stood out amongst the host of students and teachers as an authority figure, as a poet and as the publication’s editor. During these times, Ognjanov writes, that three more Macedonian youths, born in Stara Zagora, proliferate their poetic stance: Serafim Grigorov, a son of a mason from Tresonche, Evgeni Stamatov, whose father was a mason from Galichnik, and Konstantin Konjarov, also the son of a mason, relocated from Rosoki. Amongst the four, as the most gifted one in the eyes of the literary public, comes Grigorov, who was a student of the vocational high school and the editor of the publication ‘Nachalo’.